1999
DOI: 10.1136/hrt.82.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of patients treated with spinal cord stimulation for therapeutically refractory angina pectoris

Abstract: Objective-To determine morbidity and mortality characteristics in patients treated with electrical neuromodulation for refractory angina pectoris. Design-A retrospective multicentre study of patients treated with spinal cord stimulation between 1987 and 1997; 21 centres were contacted and 14 responded. Setting-Specialist centres worldwide. Patients-Questionnaires were returned on 517 patients, of whom 71% were male. One was lost to follow up. Mean (SD) age was 63.9 (10.1) years. Duration of angina pectoris was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 18 publications
6
63
1
6
Order By: Relevance
“…We applied 1-s frequencies of 4,096-32,768 Hz, introducing up to 5,000 mW into the muscles. High-frequency electrical spinal cord stimulation with implanted electrodes has previously been shown to be effective in the relief of chronic diabetic neuropathic pain [8] and several other chronic painful conditions, including back pain, phantom-limb pain, peripheral vascular disease and severe angina [19,20]. Whereas this procedure is not free of risk and may give rise to life-threatening infection [21], the HF treatment used in our study is safe and may potentially be used for other chronic pain indications.…”
Section: Discussionmentioning
confidence: 82%
“…We applied 1-s frequencies of 4,096-32,768 Hz, introducing up to 5,000 mW into the muscles. High-frequency electrical spinal cord stimulation with implanted electrodes has previously been shown to be effective in the relief of chronic diabetic neuropathic pain [8] and several other chronic painful conditions, including back pain, phantom-limb pain, peripheral vascular disease and severe angina [19,20]. Whereas this procedure is not free of risk and may give rise to life-threatening infection [21], the HF treatment used in our study is safe and may potentially be used for other chronic pain indications.…”
Section: Discussionmentioning
confidence: 82%
“…29 Another small randomized trial involved 24 patients with refractory angina. 30 Nine other studies, either retrospective [31][32][33] or prospective 29,34 -38 cohort studies, were identified in the literature. Although the results of these studies appear promising, there is still a paucity of data on the intermediateand long-term benefit of these devices.…”
Section: A Spinal Cord Stimulationmentioning
confidence: 99%
“…Furthermore, this also applies to the improvement of the quality of life, enhancement of physical performance, reduction in the use of nitroglycerine, decrease in hospitalization admissions, and reduction in pain intensity and frequency in these patients. With this regard, in 1999, Vaarwerk et al (62) presented the results of the SCS use in patients (n = 517) diagnosed with refractory angina pectoris. The study included 71% male patients (n = 367), a median follow-up was 23 months (ranging from 0 to 128), within the mean age 63.9±10.1 years.…”
Section: Results In Pain Managementmentioning
confidence: 99%